2076. Expanded Antibiotic Menu Demonstration for Novel Rapid Phenotypic Antimicrobial Susceptibility Testing Platform. (26th November 2018) - Stern, Eric; Vacic, Aleksandar; Flentie, Kelly; Spears, Benjamin; Purmort, Nathan; Giok, Felicia; DaPonte, Kayla; Scott, Sarah; Puff, Derek; Floyd, Frederick; Zhang, Zhi; Reilly, Patrick; et al.
Abstract: Background: Fast transitions to targeted therapies for infectious disease patients are paramount for optimal patient care and antibiotic stewardship. A next-generation phenotypic antimicrobial susceptibility test (AST) system that provides rapid results for broad menus of >30 antibiotics per patient sample is required. SeLux has developed a rapid, phenotypic AST platform that utilizes standard 384-well microplates. These consumables provide sufficient wells for simultaneous testing of newly approved antibiotics and broad selections of conventional antibiotics. Here, we demonstrate the platform's ability to produce fast, accurate results with newly approved and not-yet-approved antibiotics. Methods: The core of SeLux's technology is a novel assay for bacterial surface area, which enables delineation of truly resistant bacteria from organisms that filament or swell in antibiotic concentrations above the MIC. AST was performed with the SeLux platform and compared with the CLSI broth microdilution reference method. Testing of 20 representative conventional antibiotics was performed on 1, 191 isolates, including 323 FDA-CDC "challenge" strains and comprising 20 species of nonfastidious bacteria. Testing of newly developed antibiotics, generous gifts from the manufacturers, was performed with ~20 to 50 isolates with representative MICs throughout the dilution series and encompassing the breakpoint region. Results: Testing of conventional antibiotics showed essential agreements (EA) and categorical agreements (CA) ≥90% with the CLSI reference method for all combinations tested (Figures 1 and 2). The platform returned results within 6.5 hours for >98% of the isolates tested to date. The SeLux platform's EA was ≥90% for all newly developed antibiotics tested to date (Figure 3). For newly approved antibiotics, CAs were similarly ≥90% with no very major errors (Vmj). Conclusion: The SeLux platform's compatibility with 384-well microplates should transform the rate with which newly approved antibiotics gain use. By speeding the reporting of AST results, SeLux's platform will further enable hospitals to simultaneously improve patient care, decrease lengths-of-stay, and meet antibiotic stewardship goals. Disclosures: E. Stern, SeLux Diagnostics: Board Member, Employee and Shareholder, Salary. A. Vacic, SeLux Diagnostics: Employee and Shareholder, Salary. K. Flentie, SeLux Diagnostics: Employee and Shareholder, Salary. B. Spears, SeLux Diagnostics: Employee and Shareholder, Salary. N. Purmort, SeLux Diagnostics: Employee and Shareholder, Salary. F. Giok, SeLux Diagnostics: Employee and Shareholder, Salary. K. DaPonte, SeLux Diagnostics: Employee and Shareholder, Salary. S. Scott, SeLux Diagnostics: Employee and Shareholder, Salary. D. Puff, SeLux Diagnostics: Employee and Shareholder, Salary. F. Floyd Jr., SeLux Diagnostics: Employee and Shareholder, Salary. Z. Zhang, SeLux Diagnostics: Employee and Shareholder, Salary. P. Reilly, SeLux Diagnostics: Employee, Salary. J. Liu, SeLux Diagnostics: Employee, Salary. E. Viveiros, SeLux Diagnostics: Employee, Salary. N. Phelan, SeLux Diagnostics: Employee, Salary. C. Krebill, SeLux Diagnostics: Employee, Salary. A. Flyer, SeLux Diagnostics: Consultant, Scientific Advisor and Shareholder, Consulting fee. D. Smalley, SeLux Diagnostics: Scientific Advisor and Shareholder, Consulting fee. D. C. Hooper, SeLux Diagnostics: Scientific Advisor, Consulting fee. M. J. Ferraro, SeLux Diagnostics: Scientific Advisor and Shareholder, Consulting fee.